Clinical Results of Ab Interno Canaloplasty in Patients with Open-Angle Glaucoma - Hughes, Trevor (Clin Ophthalmol, 2020)
PURPOSE: To report treatment outcomes of ab interno canaloplasty using the Visco360 and Omni system devices as a standalone procedure or combined with cataract surgery in patients with open-angle glaucoma (OAG). DESIGN: Retrospective, single-center, consecutive case series. STUDY PATIENTS: Eighty-nine eyes of 64 patients aged 43 to 91 with open-angle glaucoma treated with ab interno canaloplasty between January 2018 and September 2019. Eyes with previous incisional glaucoma surgery and eyes with less than 90 degrees of viscodilation were excluded. INTERVENTION: Patients underwent ab interno canaloplasty as a stand-alone procedure or in conjunction with cataract surgery. Ab interno canaloplasty was performed with either the Visco360 or Omni System devices (Sight Sciences, Menlo Park, CA). Treatment consisted of viscodilation without trabeculotomy. MAIN OUTCOME MEASURES: Primary outcome measures were mean IOP and mean number of glaucoma medications. Additional analysis included the impact of degrees of treatment on treatment outcomes. RESULTS: Preoperative mean IOP was 24.5 ± 8.3; the number of preoperative glaucoma medications was 2.5 ± 1.3. At 18 months postoperative, the mean IOP was reduced 36% to 15.8 ± 2.5 (P<0.001) and glaucoma medications were reduced 32% to 1.7 ± 1.5 (P<0.05). Higher preoperative IOP was significantly correlated with increased IOP lowering. Reduction of mean IOP and medications were not significantly different between standalone ab interno canaloplasty vs cataract surgery/ab interno canaloplasty. Reduction of mean IOP and medications were not significantly different between patients with 180 degrees of treatment vs 360 degrees of treatment. CONCLUSION: Ab interno canaloplasty reduces IOP and glaucoma medication use in patients with OAG whether as a standalone surgery or in combination with cataract surgery.